Minor-axis flexural buckling behaviour and resistances of pin-ended S690 high strength steel welded I-section columns - Sun, Yao (2022)
The present paper reports comprehensive experimental and numerical studies of pin-ended S690 high strength steel welded I-section columns failing by flexural buckling about the minor principal axis. The testing programme was conducted on two S690 high strength steel welded I-sections, and included initial geometric imperfection measurements and ten pin-ended column tests. This was followed by a numerical modelling programme, where finite element models were firstly developed to replicate the test responses and then adopted to conduct parametric studies to generate further numerical data over a wide range of cross-section dimensions and member lengths. The obtained test and numerical data, together with the test data collected from previous literature, were analysed and employed to assess the accuracy of the relevant design rules, as given in the European code, American specification and Australian standard, for S690 high strength steel welded I-section columns failing by flexural buckling about the minor principal axis. The assessment results revealed that both the European code and Australian standard yield conservative resistance predictions for S690 high strength steel welded I-section columns failing by flexural buckling about the minor principal axis, while the American specification offers an overall satisfactory level of design accuracy, but with some over-predicted design flexural buckling resistances for those intermediate and long columns with relatively large member non-dimensional slendernesses. Finally, an improved design approach was proposed and shown to provide safe, accurate and consistent resistance predictions for S690 high strength steel welded I-section columns failing by flexural buckling about the minor principal axis.